1981
DOI: 10.1139/p81-137
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between the very low frequency chorus and pulsating aurora observed by low-light-level television at

Abstract: A good correlation was found between the very low frequency chorus and pulsating aurora observed at Park Site (L -4.4), Saskatchewan, Canada, during the recovery phase ofa substorrn on January 28, 1980. The activity of the chorus was low during the periods when the pulsating aurora was active over the station. However, seven chorus events were identified during that period and six of them showed one-to-one correlation with the brightening of a pulsating patch. The brightening of the patch leads chorus events b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 6 publications
3
31
0
Order By: Relevance
“…Koons (1981) shows, using SCATHA satellite data, that the VLF chorus emissions very often start from the frequencies inside the ELF frequency range and that the chorus emissions could be generated by natural stochastic processes occurring in strongly structured bands of ELF-hiss in the outer magnetosphere. Tsuruda et al (1981) report only six cases of peak to peak correlation between chorus elements and pulses of auroral patches during more than one hour of observation. Hansen and Scour®eld (1990) have shown that the range of delay times between VLF waves and corresponding optical pulsations is consistent with electron cyclotron source region located near the equatorial plane.…”
Section: Introductionmentioning
confidence: 92%
“…Koons (1981) shows, using SCATHA satellite data, that the VLF chorus emissions very often start from the frequencies inside the ELF frequency range and that the chorus emissions could be generated by natural stochastic processes occurring in strongly structured bands of ELF-hiss in the outer magnetosphere. Tsuruda et al (1981) report only six cases of peak to peak correlation between chorus elements and pulses of auroral patches during more than one hour of observation. Hansen and Scour®eld (1990) have shown that the range of delay times between VLF waves and corresponding optical pulsations is consistent with electron cyclotron source region located near the equatorial plane.…”
Section: Introductionmentioning
confidence: 92%
“…Chorus waves have been considered as one of the candidate wave modes that drive pulsating aurora, based on correlations between ELF/VLF intensity and auroral luminosity [Tsuruda et al, 1981;Johnstone, 1983;Tagirov et al, 1999]. Although it has been rare to observe equatorial and auroral regions simultaneously and to precisely treat magnetic field line modeling, recent studies by Nishimura et al [2010Nishimura et al [ , 2011 determined magnetic field mapping and identified uniquely that lower band chorus is responsible for driving pulsating aurora.…”
Section: Introductionmentioning
confidence: 99%
“…These waves interact with high-energy (10-100 keV) electrons and cause modulation of spectacular pulsating auroras [e.g., Tsuruda et al, 1981;Nishimura et al, 2010;Miyoshi et al, 2010;Lessard, 2012;Li et al, 2012;Ozaki et al, 2012]. ELF/VLF chorus emissions can also interact with relativistic electrons in the radiation belts, contributing to their acceleration and dissipation in the inner magnetosphere [e.g., Miyoshi et al, 2003Miyoshi et al, , 2007Katoh and Omura, 2007;Kasahara et al, 2009].…”
Section: Introductionmentioning
confidence: 99%